(untitled) (Archives of Clinical Psychiatry, 2005)
Delirium remained a stable psychiatric category until the early 19th century when it underwent etiological and phenomenological redefinition, precipitating the transformation of the functional insanities into psychoses. Confusion, introduced by French workers during the second half of the century, referred to a syndrome wider than (but including) delirium. It emphasized chaotic thinking and cognitive failure. The notion of clouding of consciousness (and temporo-spatial disorientation) established a common denominator for the two concepts, while Chaslin and Bonhoeffer redefined confusion and delirium as the stereotyped manifestations of acute brain failure.